2020
DOI: 10.1111/coa.13636
|View full text |Cite
|
Sign up to set email alerts
|

Management of new onset loss of sense of smell during the COVID‐19 pandemic ‐ BRS Consensus Guidelines

Abstract: Objectives The primary aim of the study is to provide recommendations for the investigation and management of patients with new onset loss of sense of smellduring the COVID‐19 pandemic Design After undertaking a literature review, we used the RAND/UCLA methodology with a multi‐step process to reach consensus about treatment options, onward referral andimaging. Setting and participants An expert panel consisting of 15 members was assembled. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
118
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 13 publications
1
118
0
6
Order By: Relevance
“…The reported persistence of smell/taste disturbances requires improved management guidelines, and points to the need for more treatments to be evaluated through clinical trials. At present, guidelines published by ENT UK/British Rhinological Society recommend those with recent loss of smell and Covid‐19 infection are managed by their GP with treatments suggested, which may include oral steroids after the initial 2 weeks 5 . Further guidance can be found on supportive resources such as those available through Fifth Sense (http://www.fifthsense.org.uk).…”
Section: Discussionmentioning
confidence: 99%
“…The reported persistence of smell/taste disturbances requires improved management guidelines, and points to the need for more treatments to be evaluated through clinical trials. At present, guidelines published by ENT UK/British Rhinological Society recommend those with recent loss of smell and Covid‐19 infection are managed by their GP with treatments suggested, which may include oral steroids after the initial 2 weeks 5 . Further guidance can be found on supportive resources such as those available through Fifth Sense (http://www.fifthsense.org.uk).…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 , 32 ] Since coronavirus is one of the triggers of PVOD, the effective treatment of PVOD is of great reference value for studying the treatment of smell disorders in COVID-19. [ 9 , 15 ] Present study shows that OT, as an emerging nonpharmacologic therapy option, has shown promise in the treatment of PVOD. [ 33 , 34 ] An increasing body of preclinical and clinical evidence supported the beneficial effects of OT in smell disorders.…”
Section: Discussionmentioning
confidence: 97%
“…[ 24 ] Research from Dr Borsetto D and Dr Hopkins C shows a high rate of early recovery, at 4 to 6 weeks after onset, approximately 90% patients have experienced recovery. [ 8 , 9 ] Dr Yan XG's study also suggests in patients with less than a year of smell disorders, the olfactory function improved obviously. [ 24 ] In addition, long-term OT seems to be associated with better results in patients with smell disorders than a short-term scheme.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations